Thyroid Gland 18F-FDG Uptake in Neurofibromatosis Type 1. Issue 3 (5th June 2018) - van Lierop, Zoë Y.G.J.; Jentjens, Sander; Anten, Monique H.M.E.; Wierts, Roel; Stumpel, Connie T.; Havekes, Bas; van Kroonenburgh, Marinus J.P.G.
Abstract : Purpose: To investigate thyroid gland characteristics on 18 F-FDG positron emission tomography/computed tomography (PET/CT) imaging in patients with neurofibromatosis type 1 (NF1). Subjects and Methods: Thyroid gland characteristics of patients with a clinical diagnosis of NF1 who underwent 18 F-FDG PET/CT imaging for the first time to distinguish benign neurofibroma from malignant peripheral nerve sheath tumor (MPNST) at our institution ( n = 69) were compared to PET/CT imaging of sarcoidosis ( n = 25) and early stage lung cancer (T1 N0 M0 tumors, n = 15) patients. Results: Two NF1 patients (3%) showed a diffuse 18 F-FDG uptake in the thyroid gland, 2 patients (3%) had an irregular uptake, and 7 patients (10%) had a focal uptake. Among the sarcoidosis patients, 1 showed a diffuse uptake (4%) and 1 had an irregular uptake (4%). In the early stage lung cancer group, 1 patient showed a diffuse uptake (7%) and 1 had a focal uptake (7%). NF1 patients had larger mean thyroid volume and mean SUVmax compared to sarcoidosis patients but not compared to early stage lung cancer patients. Four NF1 patients were diagnosed with multinodular goiter, 2 patients were diagnosed with benign chronic lymphocytic thyroiditis, 1 patient had metastasis to the thyroid, and 1 patient had medullary thyroid cancer. Conclusion: Even though NF1 patients did not show an increased risk of thyroid incidentaloma on PET/CT compared to previous studies on non-thyroid cancer patients, the incidence shows that awareness of possible thyroid disease is important.